Dynamique des rapports de places et des images identitaires dans Les parents terribles de Jean Cocteau - FLOREA, Ligia Stela (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
Dynamics of Place Relationships and Identity Images in Les parents terribles by Jean Cocteau. The article aims to study the dynamics of the place relationships between mother and son in scene IV of the first act of the above-mentioned play. This relationship, which represents the central theme of the play, is based on authority and domination and the son will try to ward off by resorting to a strategy. We will try to see first of all what this strategy consists of and what effect it will have on the evolution of the relationships between the two characters. Then, the study of the successive phases through which verbal interaction goes through (conversation, discussion, argument) will allow us to show how the plurality of interlocutive roles influences the dynamics of place relationships and identity images.